2005
DOI: 10.1103/physreva.72.062329
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-state transfer characterized by mode entanglement

Abstract: We study the quantum-state transfer ͑QST͒ of a class of tight-bonding Bloch electron systems with mirror symmetry by considering the mode entanglement. Some rigorous results are obtained to reveal the intrinsic relationship between the fidelity of QST and the mirror mode concurrence ͑MMC͒, which is defined to measure the mode entanglement with a certain spatial symmetry and is just the overlap of a proper wave function with its mirror image. A complementarity is discovered as the maximum fidelity is accompanie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…B a A , and O n−n+ = n − , n + | O |n − , n + denotes the average value for an arbitrary operator O ( [19]). Since states |n − , n + and |n − , n + AB ⊗ |0 , possess the same symmetry with respect to the points A and B, we have…”
Section: Reduced Density Matrix and Entanglementmentioning
confidence: 99%
“…B a A , and O n−n+ = n − , n + | O |n − , n + denotes the average value for an arbitrary operator O ( [19]). Since states |n − , n + and |n − , n + AB ⊗ |0 , possess the same symmetry with respect to the points A and B, we have…”
Section: Reduced Density Matrix and Entanglementmentioning
confidence: 99%
“…With these recognitions, it is found that modes, rather than particle labels, are universal concepts to properly describe the quantum entanglement of indistinguishable * Electronic address: songtc@nankai.edu.cn particle systems. This idea is used to characterize the ground-state entanglement of the BCS model [24] and superconductivity [23,29], and also it is investigated to derive the interesting relation between entanglement and quantum state transfer [30]. Some related works were also proposed by different authors [25,26,27,28] recently.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the subject of utilizing supercold atoms as highly reflecting mirrors has gained much attention. In particular, it has been demonstrated that a collection of cold atoms trapped near the surface of a one-dimensional waveguide can form a nearly perfect mirror for the radiation incident on the atoms [4][5][6]. The waveguide represents a photonic channel which enhances the electromagnetic field to which the atoms are coupled thereby leading to a strong collective behavior of the atoms.…”
Section: Introductionmentioning
confidence: 99%